Soil Preferential Flow Characteristics in Coal Mine Subsidence Area under Different Rainfall Duration - GUO Qiaoling; HU Qian; DAI Bin; YUAN Yizhe; PENG Zikang (Shuitu Baochi Xuebao)
[Objective] Research on the preferential flow characteristics triggered by cracks in coal mining subsidence areas can provide support for scientific and rational development of water resource management and ecological management practice in the mining area. [Methods] Three cracks of the same width (3 cm) were selected in the coal mining subsidence area of Shenfu-Dongsheng Coal Field to carry out the staining tracer test under the same rainfall intensity and different rainfall durations. Processing software such as Adobe Photoshop 2020, Image Pro Plus 6.0, SketchUp Pro 2019, and Auto CAD 2 019 were used to analyze the preferential flow characteristics of cracks under different rainfall durations. [Results] 1) Soil volumetric water content, porosity, and saturated hydraulic conductivity in the preferential flow occurrence area of the Shenfu-Dongsheng coal mining subsidence area were greater than those in the non-preferential flow area, and the volumetric weight and field water-holding capacity were less than those in the non-preferential flow area zone. 2) When the rainfall duration was 10, 20 and 30 min, the corresponding depths of substrate flow were 5, 8 and 10 cm, respectively, while the depths of preferential flow were 26.4, 47.7 and 44.3 cm, respectively. The longer the rainfall duration, the deeper the development of substrate and preferential flow. 3) The staining area ratio at each test site showed a decreasing trend with the increase of soil depth, and the morphology showed an S shape. When the rainfall duration was short, the magnitude of change in the coloring area ratio with soil depth was small; when the rainfall duration was long, the fluctuation of the coloring area ratio curve increased. 4) In general, with the increase of soil depth, the number of wide staining paths decreased, the number of fine staining paths increased, and the total number of staining paths showed a tendency of increasing first and then decreasing. The longer the rainfall duration, the wider the soil staining paths at the same depth was, and there were more wide paths. [Conclusion] The findings can provide a scientific basis for land reclamation and ecological management in coal mining areas.